Diffusion approximation algorithms in merging phase space - Koroliuk, V.; Limnios, N. (Інститут математики НАН України, 2007)
Diffusion approximation algorithms for stochastic systems in split and merging phase space are represented in servey form. The main mathematical tools of such algorithms are described in our book ”Stochastic Systems in Merging Phase Space” (World Scientific Publishing, 2005).